2018
DOI: 10.1075/japc.00011.ki
|View full text |Cite
|
Sign up to set email alerts
|

Social support and mental health

Abstract: Immigrants experience adversity and hardship in a new environment. These experiences negatively affect their psychological well-being. Online support forums are preferred channels to seek and receive social support for mental health issues. Accordingly, this study analyzed online support forums for Chinese and Korean immigrant women, focusing on different types of mental health problems, support-seeking strategies used, social support received and the relationships between them. Asian immigrant women with ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…Positive health impacts of good/helpful social support have been widely studied (Afifi et al, 2013 ; Burleson & Goldsmith, 1998 ; Ki & Jang, 2018 ; Sprecher et al, 1992 ). In a large-scale review of social support literature, Wright ( 2016 ) concluded that decades of research studies indicate that interpersonal social support provides substantial benefits to physical health and psychological wellbeing.…”
Section: Optimal Matching Model and Social Supportmentioning
confidence: 99%
“…Positive health impacts of good/helpful social support have been widely studied (Afifi et al, 2013 ; Burleson & Goldsmith, 1998 ; Ki & Jang, 2018 ; Sprecher et al, 1992 ). In a large-scale review of social support literature, Wright ( 2016 ) concluded that decades of research studies indicate that interpersonal social support provides substantial benefits to physical health and psychological wellbeing.…”
Section: Optimal Matching Model and Social Supportmentioning
confidence: 99%
“…This is especially true for people who are considering disclosing sensitive, stigmatized, or negative aspects of their personal lives, such as mental illnesses. On the positive side, individuals suffering from certain diseases are constantly seeking both informational and emotional support (e.g., Andalibi et al, 2017; De Choudhury & De, 2014; Ki & Jang, 2018; Myrick et al, 2016; Naslund et al, 2014). In addition, SNSs help individuals find patients in similar situations, family members, friends, and health care experts in a way that transcends temporal and geographical limitations (Barak et al, 2008), thus facilitating community building and enhancing the benefits of disclosure on SNSs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building on this line of thinking, we would like to take one step further and discuss community building as an important need of mental health communities on an algorithm-mediated platform. While interpersonal relationships might not be the focus of a content platform such as RED, social connections and a sense of community are sorely needed for people who suffer from mental illnesses (De Choudhury & De, 2014; Ki & Jang, 2018; Naslund et al, 2016). Thus, a question arises as to whether and how virtual communities are built on an algorithm-mediated platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cronbach's alpha value was .806. 'Caregiving to parents' was revised version of the scale used by Kim [6]. The scale of Yun-Jeong Kim (2008) was on social support.…”
Section: Measurement Toolmentioning
confidence: 99%